"To dream it is to ride the ruin": Meditations on Anti-Racism. (1st December 2021) - Mathur, Ashok; Nicholson, Cecily; Srivastava, Aruna
This conversation and later interventions occurred in late 2020 and early 2021. Ashok Mathur, Cecily Nicholson, and Aruna Srivastava discuss the politics, limits and possibilities of anti-racism a racism in recent months, particularly in educational and community contexts. We weave our histories and experiences working within anti-racism and cultural communities over many years, reflecting on generational change, COVID, privilege, alliance and the potential of creative practice.